Wideband blade monopole antenna with sleeved coaxial feed - Morrow, Ivor L.; Dingley, G. P.; Whittow, W. G.; Cooper, A. (Cranfield University, 2009)
A wideband planar monopole antenna requiring a small ground plane is described. Numerical and measured results confirms the antenna has good radiation efficiency and stable omni-directional radiation patterns over an impedance bandwidth of 4.1:1 covering the 200-850 MHz frequency spectrum.